Phytase Supplementation to Corn Germ Meal Based Low Phosphorus Diets: Growth Performance and Phosphorus Retention in Coloured Broilers - Sowjanya Lakshmi, R. Kasi; Gloridoss, R.G.; Singh, K. Chandrapal (Indian Journal of Animal Nutrition, 2018)
A study was conducted with colored (Raja-II) broilers (1-42 d of age) fed corn germ meal (CGM) based low phosphorus diets supplemented with phytase enzyme to evaluate growth performance, phosphorus retention and tibia ash content. A total of 150 day old colored broiler chicks were allotted to five treatments of30 birds in each (five replicates of six birds each). The control diet containing P at optimum level without phytase and CGM served as control. Experimental diets were prepared by replacing dicalcium phosphate in control diet with lime stone powder and by supplementing phytase enzyme (2500 IU). The diets were furtherprepared by incorporating CGM at 15, 20 and 25% to the diet supplemented with phytase (2500 IU). There was significant (P